Optical coherence tomography imaging of optic disc cavernous haemangioma. (November 2016) - Katta, Mohamed; Mehta, Hemal; Ho, Ivan; Garrick, Ray; Chong, Robert
Highlights: Cavernous haemangioma is a differential of vascular optic disc lesions. Optical coherence tomography is a useful non-invasive imaging modality to objectively follow-up these lesions. These lesions can be managed conservatively provided no sight-threatening complication develops. Abstract: Optic disc cavernous haemangiomas are either found incidentally or after presentation with vitreous haemorrhage. They are characterised by a cluster of grapes appearance to the multiple vascular saccules that make up the tumour. They are more often found in the retinal periphery but rarely occur at the optic disc. Optical coherence tomography (OCT) imaging may be a useful non-invasive imaging modality to follow-up these lesions. We present the case of an asymptomatic 60-year-old lady referred from her optometrist with a lesion overlying the optic disc and the ensuing diagnosis of cavernous haemangioma using fundus fluorescein angiography and OCT.